A Decision-Support Framework for Guiding Local Medical Device Innovation: An Innovation Systems perspective - Etuket, Maureen Dimitria (Stellenbosch : Stellenbosch University, 2026)
Thesis (PhD)--Stellenbosch University, 2026.